Liquid Levothyroxine: Efficacy and Application in the Treatment of Myxoedema Coma - A Narrative Review - Nowoświat, Patrycja; Maślankiewicz, Maria; Muzyk, Magdalena; Mrowczyk, Patrycja; Bado, Michał; Bednarczyk, Paulina; Malaka, Ewa Katarzyna; Duda, Weronika; Pilawska, Sandra Agnieszka; Goncerz, Michał; et al. (Quality in Sport, 2024)
Introduction: Myxoedema coma is a severe and rare manifestation of hypothyroidism that requires immediate and effective intervention. Traditional treatment involves the use of levothyroxine, a synthetic thyroid hormone. Liquid levothyroxine presents an alternative formulation that may offer advantages in the critical care setting, particularly when gastrointestinal absorption is impaired. Aim of the Study: This narrative review aims to evaluate the efficacy and application of liquid levothyroxine in the treatment of myxoedema coma, comparing it to other available forms and providing insights into its clinical use. Materials and Methods: A comprehensive literature search was conducted using databases such as PubMed, Medline, and Cochrane Library. Studies, clinical trials, case reports, and reviews were included if they addressed the use of liquid levothyroxine in myxoedema coma. Data were extracted and analyzed to assess the pharmacokinetics, administration protocols, outcomes, and comparative efficacy of liquid levothyroxine. Results: The review identified several key studies and case reports indicating that liquid levothyroxine offers superior bioavailability and faster onset of action compared to oral tablets, particularly in patients with compromised gastrointestinal function. Case studies demonstrated improved clinical outcomes and recovery times with liquid levothyroxine, highlighting its potential benefits in the acute management of myxoedema coma. Conclusion: Liquid levothyroxine appears to be a promising alternative for the treatment of myxoedema coma, offering enhanced absorption and rapid therapeutic effects. While preliminary data are encouraging, further research and clinical trials are necessary to establish standardized treatment protocols and confirm its efficacy. Understanding the role of liquid levothyroxine in this critical condition can enhance treatment strategies and improve patient outcomes.